Depression: relationships to sleep paralysis and other sleep disturbances in a community sample - Mariana Szklo‐Coxe; Terry Young; Laurel Finn; Emmanuel Mignot (2007)
Summary Sleep disturbances are important correlates of depression, with epidemiologic research heretofore focused on insomnia and sleepiness. This epidemiologic study’s aim was to investigate, in a community sample, depression’s relationships to other sleep disturbances: sleep paralysis (SP), hypnagogic/hypnopompic hallucinations (HH), cataplexy – considered rapid eye movement‐related disturbances – and automatic behavior (AB). Although typical of narcolepsy, these disturbances are prevalent, albeit under‐studied, in the population. Cross‐sectional analyses (1998–2002), based on Wisconsin Sleep Cohort Study population‐based data from 866 participants (mean age 54, 53% male), examined: depression (Zung Self‐Rating Depression Scale), trait anxiety (Spielberger State‐Trait Anxiety Inventory, STAI‐T ≥ 75th percentile), and self‐reported sleep disturbances. Descriptive sleep data were obtained by overnight polysomnography. Adjusted logistic regression models estimated depression’s associations with each (>few times ever) outcome – SP, HH, AB, and cataplexy. Depression’s associations with self‐reported SP and cataplexy were not explained by anxiety. After anxiety adjustment, severe depression (Zung ≥55), vis‐à‐vis Zung <50, increased SP odds ∼500% ( P = 0.0008). Depression (Zung ≥50), after stratification by anxiety given an interaction ( P = 0.02), increased self‐reported cataplexy odds in non‐anxious (OR 8.9, P = 0.0008) but not anxious (OR 1.1, P = 0.82) participants. Insomnia and sleepiness seemed only partial mediators or confounders for depression’s associations with self‐reported cataplexy and SP. Anxiety (OR 1.9, P = 0.04) partially explained depression’s (Zung ≥55) association with HH (OR 2.2, P = 0.08). Anxiety (OR 1.6, P = 0.02) was also more related than depression to AB. Recognizing depression’s relationships to oft‐neglected sleep disturbances, most notably SP, might assist in better characterizing depression and the full range of its associated sleep problems in the population. Longitudinal studies are warranted to elucidate mediators and causality.